Brainstem biopsy in pediatric diffuse intrinsic pontine glioma in the era of precision medicine: the INFORM study experience. (June 2019) - Pfaff, Elke; El Damaty, Ahmed; Balasubramanian, Gnana Prakash; Blattner-Johnson, Mirjam; Worst, Barbara C.; Stark, Sebastian; Witt, Hendrik; Pajtler, Kristian W.; van Tilburg, Cornelis M.; Witt, Ruth; Milde, Till; Jakobs, Martin; et al.
Abstract: Purpose: Diffuse intrinsic pontine glioma (DIPG) is a highly aggressive paediatric brain tumour with fatal outcome. The Individualised Therapy For Relapsed Malignancies In Childhood (INFORM) registry study offers comprehensive molecular profiling of high-risk tumours to identify target alterations for potential precision therapy. We analysed molecular characteristics and clinical data after brainstem biopsy of all enrolled newly diagnosed DIPGs. Patients and methods: From –February 2015 to February 2018, 21 subsequent primary DIPG cases were enrolled in the nation-wide multicentre INFORM registry study after brainstem biopsy. Whole-genome, whole-exome sequencing and DNA methylation analysis were performed, and RNA-sequencing was added in case of sufficient material. Clinical data were obtained from standardised questionnaires and the INFORM clinical data bank. Results: Tumour material obtained from brainstem biopsy was sufficient for DNA analysis in all cases and RNA analysis in 16 of 21 cases. In 16 of 21 cases (76%), potential targetable alterations were identified including highly relevant MET  and NTRK1 fusions as well as an EZH2 alteration not previously described in DIPG. In 5 of 21 cases, molecular information was used for initiation of targeted treatment. The majority of patients (19/21) presented with neurological deficits at diagnosis. Newly arising or worsening of neurological deficits post-biopsy occurred in nine patients. Symptoms were reversible or improved notably in eight cases. Conclusion: In this multicentre study setting, brainstem biopsy of DIPG was feasible and yielded sufficient material for comprehensive molecular profiling. Relevant molecular targets were identified impacting clinical management in a substantial subset. Death or severe bleeding occurred in none of the cases. One of 20 patients experienced unilateral paraesthesia possibly related to biopsy. Highlights: Brainstem biopsies of DIPG are relatively safe in a 'real life' setting involving multiple centres. Full range of state-of-the-art molecular characterisation is feasible in a rapid turnaround time. Actionable targets are identified in the majority of cases with clinical impact in some cases.